2022
DOI: 10.15584/ejcem.2022.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and nitrosative stress in patients with meningitis

Abstract: Introduction and aim. Meningitis is an acute inflammation of the protective membranes covering the brain and spinal cord, known as the meninges. In this study, oxidative and nitrosative stress were evaluated in cerebrospinal fluid (CSF) and blood samples that were taken from patients with meningitis. Our goal was to identify a fast and a reliable biomarker using these parameters in order to the early diagnose of bacterial meningitis. Material and methods. In this study, 37 bacterial meningitis, 30 tuberculous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The pathogenesis of AD and CU is not fully understood; however, significant progress has been made in recent years. Oxidative stress, defined as an imbalance between the generation of reactive oxygen species (ROS) and the mechanisms of their elimination, accompany many diseases, including psoriasis, asthma, cystic fibrosis, neurodegenerative diseases, and cancer [ 9 , 10 , 11 , 12 , 13 ]. Oxidative stress leads to lipid peroxidation, protein oxidation, and DNA damage, thus inducing several physiological dysfunctions and loss of biological activity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of AD and CU is not fully understood; however, significant progress has been made in recent years. Oxidative stress, defined as an imbalance between the generation of reactive oxygen species (ROS) and the mechanisms of their elimination, accompany many diseases, including psoriasis, asthma, cystic fibrosis, neurodegenerative diseases, and cancer [ 9 , 10 , 11 , 12 , 13 ]. Oxidative stress leads to lipid peroxidation, protein oxidation, and DNA damage, thus inducing several physiological dysfunctions and loss of biological activity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Vitro Antimicrobial Activity of CuNPs against S. aureus. In the present study, antimicrobial activity of CuNPs was evaluated by in vitro antimicrobial activity on pure culture of S. aureus (ATCC, 25293) which is one of the major mastitis-causing pathogens identified and isolated from clinical cases of bovine mastitis in Kashmir valley as reported from earlier studies [40,41]. On antibiogram analysis, pure culture of S. aureus showed susceptibility to Oxytetracycline, Enrofloxacin, gentamicin, and Ceftriaxone but showed a high degree of resistance to penicillin G and intermediate degree of resistance to Amoxyclav (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In Vitro Cytotoxicity Assay for CuNPs. The MTT assay in the present study was conducted based on findings of earlier studies that compared four commonly used in vitro cytotoxicity assays to determine their ability to detect early cytotoxic events and concluded that MTT assays are the most sensitive assays in detecting cytotoxic events compared to LDH leakage, neutral orange, and protein assay [40,[44][45][46]. Furthermore, the dose-dependent cytotoxicity of CuNPs reported in the present study is in concurrence with [47,48], who reported the genotoxic potential of copper oxide nanoparticles on human pulmonary epithelial cell line Values with different superscripts differ significantly (P < 0:05) from each other.…”
Section: 2mentioning
confidence: 99%
“…To further improve BM treatment and prognosis, a better understanding is needed of the pathophysiological events that occur after activation of the host´s inflammatory pathways. There is a substantial body of work indicating high CSF levels of reactive oxygen and nitrogen species, and of antioxidants in BM patients, but the literature is very heterogeneous as determination of their concentrations has been carried out by various means [ 3 , 15 , 16 , 17 , 18 , 19 , 20 ]. Our study group has assessed the oxidative/nitrosative stress occurring in pediatric BM patients by determining biomarkers indicating oxidative/nitrosative damage to proteins in the CSF at admission to hospital [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant treatments to counteract the reactive oxygen and nitrogen species released have been studied as adjuvant treatment, among other treatments, in experimental BM models, but not in patients [ 22 , 23 ]. Only a limited number of human studies are available on oxidative stress in relation to outcome [ 18 , 19 , 20 , 24 ]. Here, we aimed to study the relation of CSF protein oxidation biomarker levels to the course and outcomes of BM.…”
Section: Introductionmentioning
confidence: 99%